Endocannabinoids Released in the Ventral Tegmental Area During Copulation to Satiety Modulate Changes in Glutamate Receptors Associated With Synaptic Plasticity Processes - Rodríguez-Manzo, Gabriela; González-Morales, Estefanía; Garduño-Gutiérrez, René (Frontiers in Synaptic Neuroscience, 2021)
Endocannabinoids modulate mesolimbic (MSL) dopamine (DA) neurons firing at the ventral tegmental area (VTA). These neurons are activated by copulation, increasing DA release in nucleus accumbens (NAcc). Copulation to satiety in male rats implies repeated ejaculation within a short period (around 2.5 h), during which NAcc dopamine concentrations remain elevated, suggesting continuous neuronal activation. During the 72 h that follow copulation to satiety, males exhibit long-lasting changes suggestive of brain plasticity processes. Enhanced DA neuron activity triggers the synthesis and release of endocannabinoids (eCBs) in the VTA, which participate in several long-term synaptic plasticity processes. Blockade of cannabinoid type 1 receptors (CB1Rs) during copulation to satiety interferes with the appearance of the plastic changes. Glutamatergic inputs to the VTA express CB1Rs and contribute to DA neuron burst firing and synaptic plasticity. We hypothesized that eCBs, released during copulation to satiety, would activate VTA CB1Rs and modulate synaptic plasticity processes involving glutamatergic transmission. To test this hypothesis, we determined changes in VTA CB1R density, phosphorylation, and internalization in rats that copulated to satiety 24 h earlier as compared both to animals that ejaculated only once and to sexually experienced unmated males. Changes in glutamate AMPAR and NMDAR densities and subunit composition and in ERK1/2 activation were determined in the VTA of males that copulated to satiety in the presence or absence of AM251, a CB1R antagonist. The CB1R density decreased and the proportion of phosphorylated CB1Rs increased in the animals that copulated compared to control rats. The CB1R internalization was detected only in sexually satiated males. A decrease in α-amino-3-hydroxy-5-methylisoxazole-4-propionate receptor (AMPAR) density, blocked by AM251 pretreatment, and an increase in the proportion of GluA2-AMPARs occurred in sexually satiated rats. GluN2A- N-methyl-D-aspartate receptor (NMDAR) expression decreased, and GluN2B-NMDARs increased in these animals, both of which were prevented by AM251 pre-treatment. An increase in phosphorylated ERK1/2 emerged in males copulating to satiety in the presence of AM251. Results demonstrate that during copulation to satiety, eCBs activate CB1Rs in the VTA, producing changes in glutamate receptors compatible with a reduced neuronal activation. These changes could play a role in the induction of the long-lasting physiological changes that characterize sexually satiated rats.